Germinal Center T Follicular Helper Cells (GC T(FH)) are Highly Permissive to HIV-1 and Alter Their Phenotype During Virus Replication - Kohler, Stephanie L. (J Immunol, 2016)
HIV-1 replication is concentrated within CD4+ T cells in B-cell follicles of secondary lymphoid tissues during asymptomatic disease. Limited data suggest that a subset of T follicular helper cells (T(FH)) within germinal centers (GC) is highly permissive to HIV-1. Whether GC T(FH) are the major HIV-1 virus-producing cells in vivo has not been established. Here, we investigated T(FH) permissivity to HIV-1 ex vivo by spinoculating and culturing tonsil cells with HIV-1 GFP reporter viruses. Using flow cytometry, higher percentages of GC T(FH) (CXCR5(high)PD-1(high)) and CXCR5+PD-1(low) cells were GFP+ than non-GC T(FH) (CXCR5+PD-1(intermediate)) or extrafollicular (CXCR5-) cells. When sorted prior to spinoculation, however, GC T(FH) were substantially more permissive than CXCR5+PD-1(low) or extrafollicular cells, suggesting that many GC T(FH) transition to a CXCR5+PD-1(low) phenotype during productive infection. In situ hybridization on inguinal lymph node sections from untreated HIV-1-infected individuals without AIDS revealed higher frequencies of HIV-1 RNA+ cells in GC than non-GC regions of follicle or extrafollicular regions. Superinfection of HIV-1-infected individuals’ lymph node cells with GFP reporter virus confirmed the permissivity of follicular cells ex vivo. Lymph node immunostaining revealed 96% of CXCR5+CD4+ cells were located in follicles. Within sorted lymph node cells from four HIV-infected individuals, CXCR5+ subsets harbored 11- to 66-fold more HIV-1 RNA than CXCR5-subsets, as determined by RT PCR. Thus, GC T(FH) are highly permissive to HIV-1, but downregulate PD-1 and to a lesser extent CXCR5 during HIV-1 replication. These data further implicate GC T(FH) as the major HIV-1-producing cells in chronic asymptomatic HIV-1 infection.